Handbook of Bereavement Research: Consequences, Coping, and Care. 2001
DOI: 10.1037/10436-021
|View full text |Cite
|
Sign up to set email alerts
|

Grief and emotion: A social–functional perspective.

Abstract: There is little doubt that for most people the death of a loved one is an intensely painful experience. However, there are considerable individual differences in duration and severity of grief (Bonanno & Kaltman, 1999;Wortman & Silver, 1989). Traditionally, bereavement theorists have assumed that recovery from loss is predicated on the concerted review and expression of the negative emotions brought about by grieving. This process, considered part of the "work" of mourning, is thought to foster acceptance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 76 publications
0
41
0
2
Order By: Relevance
“…Although the value of emotional disclosure in the amelioration of grief is arguable (Archer, 1999), particularly with regard to the value of expressing negative emotions (Bonanno, 2001), one necessary but not sufficient condition for effective counseling should be the correct identification of each troublesome emotion, not withstanding that shame and envy, in particular, may be difficult to identify in everyday discourse and "analyze" in psychotherapy (Bourne, 1968;Farber, 1976a;Foster, 1972;Lewis, 1971;Retzinger, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the value of emotional disclosure in the amelioration of grief is arguable (Archer, 1999), particularly with regard to the value of expressing negative emotions (Bonanno, 2001), one necessary but not sufficient condition for effective counseling should be the correct identification of each troublesome emotion, not withstanding that shame and envy, in particular, may be difficult to identify in everyday discourse and "analyze" in psychotherapy (Bourne, 1968;Farber, 1976a;Foster, 1972;Lewis, 1971;Retzinger, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…If Bonanno (2001) is correct and "recovery [from bereavement] is most likely to occur when negative griefrelated emotions are regulated or minimized" (p. 493), then dysregulated personality traits based on one or more problematic emotions should have important relationships with maternal grief. In support of this claim, previous research has shown that personality guilt-and shame-proneness explain a substantial proportion of the variance in maternal grief following perinatal bereavement (Barr, 2004).…”
mentioning
confidence: 99%
“…(See Table 7) This phase paralleled the group development stages of differentiation and separation (Garland et al, 1973), as well as "performing and adjourning" (Tuckman, 1965). Protective factors were identified and maximized, such as gaining the ability to regulate and minimize negative grief-related emotions and behaviors, and to instigate and enhance positive emotions (Bonanno, 2001). There was a continuation of group cohesion as the girls further explored issues of intimacy and trust by sharing their work around the use of ritual as it related to their experience of the death of a peer (Doka, 2002;.…”
Section: Adolescent Grief and Loss (Agl) Group Structurementioning
confidence: 99%
“…Finally, experimenting and expressing emotional reactions of anger, bitterness or intense guilt predicts long-term complications in the adequate resolution of bereavement except in those mourners who have maintained very contentious relationships with the deceased (Bonanno, 2001b).…”
Section: Personal Factorsmentioning
confidence: 99%
“…The use of drugs for the treatment of complicated grief should be approached carefully for two main reasons: first, because empirical research is inconclusive about the effects of drugs on the intensity of grief; and second, because it could create counterproductive addictions (Barreto & Soler, 2007;Raphael et al, 2001/2001b, Worden, 1991/1997Lacasta & Sastre, 2000).…”
mentioning
confidence: 99%